(3JMbjb GdbjGSs - (3GdWHGWHGFj, GdcGXej, GdMGFQj, GdCUHgGfj, Ydj Hf eMeO Ydj Hf CHj GdeYGdj, J (B1231 (3gs
(3ChdgG (B:s
(3HSe Gddg (B... (3JMbjb aj GdbjGS (B..(3hgh JJeI MGTjI cJHJgG Ydi GdPNjQI hgh Gfg EPG hQO Mce HLRFjf aEf cGf HGdGWdGY Ydjg jage hjJHGOQ Mce LRFjf BNQ ageG YQVjG hjJHGOQ eJUQaG jchf Pdc GdMce (B...s
(3BNQgG (B:s
.. (3heeG PcQfG XgQ MGd efUhU GdYdI hGdcdGe ajg GdcdGe hdYdc HedGMXI eG PcQfG JbOQ Ydi GdbHjM hGdSbje HGdfSHI Edi SGFQ eG GQJcHg GdabgGA ef GdJYOjGJ Yf ehVY GdfU (B.. (3hGddg Gdehabs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\ 17s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3CUhd Gdabgs